William of Malmesbury on Pagan Slavic Oracles: New Sources for Slavic Paganism and Its Two Interpretations William iz Malmesburyja o prerokbah poganskih Slovanov: nov vir o slovanskem poganstvu in njegovi interpretaciji - Słupecki, Leszek Paweł; Zaroff, Roman (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article brings to the attention of the scholarly world a hardly known medieval source Gesta Regum Anglorum written by William of Malmesbury. Who was an early 12th century English benedictine monk from Malmesbury in Western England. The article revolves around the outmost relevance of William of Malmesbury to the study of pre-christian Slavic religion, and provides two interpretations of William’s account.